1991
DOI: 10.2337/diab.40.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Media Conditions, Insulin, and Dexamethasone on Insulin-Receptor mRNA and Promoter Activity in HepG2 Cells

Abstract: Numerous physiological agents and conditions modulate cellular insulin sensitivity by downregulating or upregulating total cellular insulin receptors. In this study, we examined the effects of replacing complete medium in the absence or presence of insulin on the regulation of insulin-receptor gene expression in cultured human hepatoma cells (HepG2). Failure to replace complete medium resulted in growth arrest of HepG2 cells and a six- to sevenfold increase in insulin-receptor mRNA due to the prolongation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…As tissue-specific differences in response occur alongside alterations in circulating insulin concentration, insulin may not be the only factor in the control of the level of insulin-receptor mRNA. Indeed, it has been demonstrated in vitro in human cell lines that insulin-receptor mRNA levels are reduced by depletion of glucose levels (Briata et al 1990;Levy et al 1991), but at present it is not possible to relate this observation to the situation in vivo described here.…”
Section: Discussionmentioning
confidence: 64%
“…As tissue-specific differences in response occur alongside alterations in circulating insulin concentration, insulin may not be the only factor in the control of the level of insulin-receptor mRNA. Indeed, it has been demonstrated in vitro in human cell lines that insulin-receptor mRNA levels are reduced by depletion of glucose levels (Briata et al 1990;Levy et al 1991), but at present it is not possible to relate this observation to the situation in vivo described here.…”
Section: Discussionmentioning
confidence: 64%
“…As expected from the short half-life (2-4 h) (20,24,43) of the insulin receptor mRNA, ACT D treatment of control rats led to a marked decrease, on Northern blots, in the intensity of both the 9.5 and 7.5 kb insulin receptor mRNA species (Fig. 1, right lane).…”
Section: Resultsmentioning
confidence: 70%
“…Based on ACT D and in vitro transcription studies, it has been shown previously that the stimulatory effect of glucocorticoids on insulin receptor mRNA in human IM-9 lymphocytes also occurs at the transcriptional level (24,43). It is not known, however, whether the insulin-induced decrease in insulin receptor mRNA levels seen in rat pancreatic acinar cells (19) and Hep G2 cells (20,21) also involves a change in receptor gene transcription.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The insulin receptor promoter has many similarities to the SV40 promoter. Both are bidirectional promoters with multiple transcriptional start sites (5,10,24). Both promoters contain multiple elements that bind Spl (10,25).…”
Section: Discussionmentioning
confidence: 99%